Morphometric variation and genetic relationship of Coptotermes spp. (Blattodea: Rhinotermitidae) in Sarawak, Malaysia - Norsyarizan Jamil; Wan Nurainie Wan Ismail; G. Veera Singham (Penerbit Universiti Kebangsaan Malaysia, 2018)
Amongst the termite genera within Rhinotermitidae, the genus Coptotermes is probably regarded as one of the most destructive pest in Malaysia as it contributes to more than 90% of the damages in buildings and structures. In this study, 17 parameters were used for morphometric analysis. Partial sequence of mitochondrial DNA cytochrome oxidase subunit II (COII) was obtained from 21 populations of C. curvignathus, seven populations of C. sepangensis and two populations of C. kalshoveni in Sarawak. In addition, 11 sequences of Coptotermes spp. were obtained from GenBank and included in the analysis. Based on Discriminant Function Analyses (DFA), the maximum width of postmentum (MxWPt) is identified as the best morphological character for differentiating the four species of Coptotermes in this study, proved by canonical discriminant function. Phylogenetic analyses of COII found that C. sepangensis and C. kalshoveni are nested within a single clade. Morphological comparison also showed these two species to be identical in terms of body measurements and diagnostic features. These evidence indicates that C. sepangensis and C. kalshoveni are the same species, thus we suggest C. sepangensis is a junior synonym of C. kalshoveni.